استخدام القياس المتوازن للأداء لتقييم خدمات القطاع المصرفي السعودي في ظل حوكمة الأداء الإستراتيجي بالتطبيق على البنوك التجارية السعودية - ملو العين، علاء محمد عبدالله (جامعة الشارقة, 2015)
The present study aims mainly to evaluate and develop the balance scorecard approach adopted by Saudi commercial banks for the sake of improving the strategic performance of Saudi banking sector. To achieve this objective, the study relied on 59 questionnaires (sample of this Study) which had been collected from various managers of different Saudi commercial banks. The study adopted a several appropriate statistical methods to achieve its objectives i.e mean, frequency tables, chi-square test, etc. The study has a vital importance because it provides objective indicators which will contribute to improve the performance of Saudi banking sector as it is one of the most important sectors in achieving economic and social development. The study reached several important results including: there is a growing need to use the model of balanced scorecard in evaluating Saudi commercial banks in the light of strategic performance governance; moreover the study concluded that the necessary components to make the implementation of balanced scorecard model are provided in Saudi commercial banks. Also, the study concluded that Saudi commercial banks are committed to implement the balanced scorecard model with all of its four basic dimensions (financial – customers – Internal processes - learning & innovation). Finally, the study concluded that adding "dimension of community partnership" to those four dimensions will contribute in improving the quality performance measurement of Commercial banks accurately as it will provide new indicators which will reflect the relation of Saudi commercial banks with the community in the frame of its social responsibility.
هدفت هذه الدراسة إلى تقييم وتطوير مقياس بطاقة الأداء المتوازن بهدف تحسين الأداء الاستراتيجي للقطاع المصرفي السعودي. ولتحقيق هذا الهدف اعتمدت الدراسة على استقصاء آراء عينة بلغ عددها (59) مفردة مكونة من مديري الإدارات المختلفة بالبنوك التجارية السعودية. كما اعتمدت الدراسة كذلك على مجموعة من المقاييس الإحصائية لتحقيق أهداف الدراسة، كالمتوسطات الحسابية والجداول التكرارية واختبار (Chi-Square Test)، وتنبع أهمية الدراسة من توفيرها لمؤشرات موضوعية قد تساهم في تحسين أداء القطاع المصرفي السعودي كأحد القطاعات الهامة في تحقيق التنمية الاقتصادية والاجتماعية. وقد خلصت الدراسة إلى عدد من النتائج منها: أن هناك حاجة متزايدة لاستخدام نموذج بطاقة الأداء المتوازن في تقييم أعمال المصارف التجارية السعودية في ضوء حوكمة الأداء الاستراتيجي، كما توصلت الدراسة إلى أن المقومات اللازمة لنجاح تطبيق نموذج القياس المتوازن للأداء تتوافر في المصارف التجارية السعودية، كما أظهرت نتائج الدراسة أن المصارف التجارية السعودية تلتزم بتطبيق نموذج القياس المتوازن للأداء بأبعاده الأربعة الأساسية (البعد المالي، بعد العملاء، بعد العمليات الداخلية، بعد التعليم والنمو)، وأخيرا خلصت نتائج الدراسة إلى أن إضافة بعد الشراكة المجتمعية إلى الأبعاد الأربعة الأساسية لنموذج القياس المتوازن للأداء سوف يساهم في تحسين جودة قياس الأداء في المصارف التجارية من خلال توفيره لمؤشرات جديدة تعكس علاقة المصارف التجارية السعودية بالمجتمع في إطار مسئوليتها الاجتماعية.
Keywords: قياس الأداء -- القطاع المصرفي -- الحوكمة -- الخدمات المصرفية -- الأداء المالي -- البنوك التجارية -- السعودية